Moray Mazes: The World of Corporate ManagersMoray Mazes: The World of Corporate Managers, by Jackall Robert. New York: Oxford University Press. 1988. 249 pp., $21.95, cloth. - Doherty, Elizabeth M. (Academy of Management Review, 1990)
The article reviews the book ?Moral Mazes: The World of Corporate Managers,? by Robert Jackall.